The Effect of Stress and Work Environment on the Performance of Civil Servants at the Serpong South of Tangerang District Office - Iis Munawaroh; Ana Septia Rahman (Kusuma Negara Business School, 2022)
This study aims to determine how the influence of stress and work environment on the performance of civil servants at the Serpong District Office, to find out how the influence of stress and work environment on the performance of civil servants at the Serpong district office. The method used in this study is a quantitative method, namely through approaches, data collection and analysis using statistics. The data used are observation techniques, questionnaires (a questionnaire of 58 respondents) and literature. The analytical methods used in this research are validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, simple linear regression test, multiple linear regression test, correlation coefficient test, determination test and significant test (t test and test). f). The significant value of F is 0.000 (<0.05), so it can be concluded that the hypothesis is accepted, meaning that the stress and work environment variables have a significant effect on the performance of Civil Servants. The value of R (correlation coefficient) is 0.254. So it can be interpreted that the degree of relationship between the variables of stress and work environment on employee performance is a very strong correlation. The value of the coefficient of determination (R) is obtained at 86.5%. While the remaining 13.5% is influenced by other factors not discussed in this study. It is known that the significant value for the effect of X1 (stress) on Y (employee performance) is 0.000 < 0.05 and the t value is 17.838 > 1.673, so it can be concluded that Ha_1 is accepted which means that there is an effect of X1 on Y. work) on Y (employee performance) is 0.000 < 0.05 and the t value is 2.471 > 1.673, so it can be concluded that Ha_2 is accepted which means there is an effect of X2 on Y. It is known that the significant value for the effect of X1 (stress) on Y (employee performance) is 0.000 < 0.05 and the t value is 17.838 > 1.673 and it is known that the significant value for the effect of X2 (work environment) on Y (employee performance) is 0.000 < 0.05 and the t value is 2.471 > 1.673, so it can be concluded that Ha_1 and Ha_2 are accepted meaning there is an effect of X1 and X2 on Y together. This means that stress and the work environment have quite a role in improving employee performance at the Serpong District Office.